Factores de incumplimiento del plazo de investigación preliminar en la fiscalía de violencia contra la mujer e integrantes del grupo familiar de Maynas, 2022 - Aquino Carpio, Milagros Goyzuet (2025)
The present investigation aims to describe whether the Specialized Corporate Prosecutor's Office for Crimes of Violence against Women and Members of the Family Group of Maynas complied in 2022 with investigating within the period established as a preliminary investigation, to establish if there was a deficit of administrative and fiscal personnel that made it difficult to meet the preliminary investigation deadline in 2022, to establish if the administrative and fiscal personnel were trained in the areas of gender law, gender violence and fiscal office management, and to establish if the extensive geography of the province of Maynas made it difficult to meet the preliminary investigation deadline in 2022. The type of research is documentary, with a qualitative approach, descriptive design, the study population consists of thirty-nine fiscal files that will be analyzed using the documentary analysis technique supported by the filing technique, the structured interview was also used. The findings revealed that the Prosecutor's Office has not met the investigation deadlines for preliminary investigations in 2022, that there is a shortage of administrative and prosecutorial staff, and that the administrative and prosecutorial staff providing services are not trained in gender law, gender-based violence, and prosecutorial office management. The vast geography of the province of Maynas made it difficult to meet the preliminary investigation deadline in 2022.